Ab-initio calculation and experimental observation of room temperature ferromagnetism in 50 keV nitrogen implanted rutile TiO2. (9th February 2018) - Luitel, Homnath; Chakrabarti, Mahuya; Sarkar, A; Dechoudhury, S; Bhowmick, D; Naik, V; Sanyal, D
Abstract: Room temperature magnetic properties of 50 keV N 4+ ion beam implanted rutile TiO2 have been theoretically and experimentally studied. Ab-initio calculation under the frame work of density functional theory has been carried out to study the magnetic properties of the different possible nitrogen related defects in TiO2 . Spin polarized density of states calculation suggests that both Ninst and NO can induce ferromagnetic ordering in rutile TiO2 . In both cases the 2p orbital electrons of nitrogen atom give rise to the magnetic moment in TiO2 . The possibility of the formation of N2 molecule in TiO2 system is also studied but in this case no significant magnetic moment has been observed. The magnetic measurements, using SQUID magnetometer, results a ferromagnetic ordering even at room temperature for the 50 keV N 4+ ion beam implanted rutile TiO2 .